2021
DOI: 10.3390/pharmaceutics13122180
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Membrane and Cell Wall Action of Antimicrobial Cyclic Lipopeptides: Modulation of the Spectrum of Activity

Abstract: Antibiotic resistance is a major public health challenge, and Gram-negative multidrug-resistant bacteria are particularly dangerous. The threat of running out of active molecules is accelerated by the extensive use of antibiotics in the context of the COVID-19 pandemic, and new antibiotics are urgently needed. Colistin and polymyxin B are natural antibiotics considered as last resort drugs for multi-resistant infections, but their use is limited because of neuro- and nephrotoxicity. We previously reported a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The vVS identified several cyclopeptides as potential binders of either BS1 or BS2, amongst which polymyxin B (PMX, Figure 2) represented the best-ranked hit for both BS1 and BS2 and thus, it was selected for further evaluation. PMX is a naturally occurring amphiphilic lipopeptide produced by fungi (although first isolated by Bacillus polymyxa) as a secondary metabolite and it is currently used as a last-resort antibiotic drug for the treatment of Gram-negative multidrug-resistant bacteria, or in topical antibiotic applications [43][44][45]. Its structure features an N-terminating methyloctanoyl linear tripeptide anchored to a cycloheptapeptide ring; the presence of this cyclic restraint together with non-canonical amino acid residues, including six L-α,γdiaminobutanoic acid residues (Dab) and one D-series residue (D-Phe), qualify it as a natural peptidomimetic [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vVS identified several cyclopeptides as potential binders of either BS1 or BS2, amongst which polymyxin B (PMX, Figure 2) represented the best-ranked hit for both BS1 and BS2 and thus, it was selected for further evaluation. PMX is a naturally occurring amphiphilic lipopeptide produced by fungi (although first isolated by Bacillus polymyxa) as a secondary metabolite and it is currently used as a last-resort antibiotic drug for the treatment of Gram-negative multidrug-resistant bacteria, or in topical antibiotic applications [43][44][45]. Its structure features an N-terminating methyloctanoyl linear tripeptide anchored to a cycloheptapeptide ring; the presence of this cyclic restraint together with non-canonical amino acid residues, including six L-α,γdiaminobutanoic acid residues (Dab) and one D-series residue (D-Phe), qualify it as a natural peptidomimetic [40].…”
Section: Resultsmentioning
confidence: 99%
“…The PMX structure was adopted as an ideal peptidomimetic (PM) starting platform, upon which new PM molecules could be built up for exploring the chemical space around the targeted PPI. Interestingly, PMX and analogues have long been the focus of intense research into the creation of new antibiotics that are effective at overcoming antimicrobial resistance [44,45]; however, to the best of our knowledge, this is the first example where PMX is used as a starting scaffold to construct PMs (resembling yet structurally different from PMX) to combat SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…27 As previously mentioned, increasing the hydrophobicity of peptides contributes to increasing their membrane permeation in Gram-positive bacteria. 28,29 Therefore, we conducted further investigations to explore whether introducing a hydrophobic amino acid mutation at position 1 could broaden the narrowspectrum antibacterial activity of GG3A1. The results demonstrated that the overall hydrophobicity of the derived peptides, with hydrophobic amino acids substituted at position 1, exhibited an overall increase in hydrophobicity compared with that of the peptide GG3A1; however, most of them remained inactive against the tested Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there are some examples where the antimicrobial agents avert solutes from passing through the outer membrane of Gram-negative bacteria, resulting in their lethality [ 14 ]. The lipid components of biological membranes are not distributed equally throughout the membrane but supplemented in specific domains, and this dispersal is altered by clustering anionic lipids with cationic peptides with multiple positive charges [ 15 17 ]. This could be harmful to bacteria, since it prevents lipids from interacting with other molecular components of the cell membrane, disrupts existing natural domains, or creates phase boundary defects between the clustered lipids and the bulk of the membrane [ 18 ].…”
Section: Introductionmentioning
confidence: 99%